EU Paediatric Investigation Plans (Pips) Might Harm Children - Rose K. (Sciendo, 2018)
Aim/objective: Since 2007, companies in the EU must submit paediatric investigation plans (PIPs) for new drugs, unless the PIP is waived and the review article investigated if that improve the child healthcare. Methods: We analysed the EU Paediatric Regulation (EUPR), PIP decisions, PIP decision patterns, EU key documents on "better medicines for children" and examined PIP studies versus the epidemiology described in the reference literature. We examined how PIPs translate into studies by checking www. clinicaltrials.gov and www.clinicaltrialsregister.org. We also investigated the medical sense of PIP-demanded clinical studies in adolescents. Results: The EUPR in Art. 2 (1) defines “paediatric population” as those between birth and 18 years. It lists challenges in dosing and safety of drugs in neonates and infants as if these challenges apply to anybody < 18 years. PIPs demand studies in adolescents although this group needs separate dose finding and efficacy studies only in exceptional cases, if at all. Most PIP studies in rare diseases are unfeasible: too many studies for too few patients in general. Two questionable PIP studies were discontinued in 2016, in one of them several patients died. Conclusions: Neonates and infants have immature organs, with resulting potential for drug over/underdosing. PIPs equalize the legal definition of childhood with a biological limit. The resulting automatism leads to a worldwide threat to children. Most PIP-demanded studies are medically senseless, some even worse. Ethics committees should reject questionable PIP studies and suspend such ongoing studies immediately.